(untitled) (The Review of Diabetic Studies, 2025)
Tuberculosis remains a leading global health threat, with household contacts carrying the highest risk of infection. Community-based interventions have been proposed to close gaps in early detection, preventive therapy, and treatment adherence. This research conducted, conducted according to PRISMA guidelines, synthesised 32 studies identified through Scopus. Interventions examined included active case finding, chemoprophylaxis, health education, community-supported DOTS, and multi-sectoral support. Findings demonstrate that integrated strategies significantly improve case detection, enhance uptake and completion of tuberculosis preventive treatment, and strengthen adherence, particularly when delivered by trained community health workers. Social protection measures further increased equity and sustainability. Despite promising outcomes, heterogeneity in study designs and limited randomised trials constrain generalizability. Scaling up locally adapted, integrated approaches remains central to achieving global TB elimination targets.